Associated factors in the attitude of students without disabilities towards the inclusion of students with disabilities in the Physical Education class: a systematic review - Rocuant Urzúa, Adolfo; Treviño Villarreal, Ernesto; Ocete Calvo, María del Carmen (Revista Complutense de Educación, 2024)
INTRODUCTION. The attitude of students without disabilities (SWD) has been considered a key element in achieving inclusion of learners with disabilities (SD). However, the field of Physical Education (PE) lacks a literature review focusing on factors associated with the formation of inclusive attitudes of SWD. This review addresses this limitation by answering the following question: What does the literature report on the main factors associated with SWD attitudes towards SD inclusion in PE? METHOD. To answer this question, the PRISMA guideline requirements were considered as a reference and 25 studies from the Web Of Science and Scopus databases were analysed. RESULTS. This review allowed us to report results in five categories: intervention programmes, difference between women and men, previous contact, competitiveness and age. CONCLUSIONS. The results indicate that intervention programmes are the main factor used in the promotion of inclusive attitudes, the difference between women and men reaffirms a tendency in favour of women, previous contact with SD is not conclusive and requires further analysis, the level of competitiveness seems to act as a constraint and age would present a positive trend.